THE VALUE OF MAGNETIC RESONANCE IMAGING FOR RECTAL CANCER STAGING TREATMENT BY LAPAROSCOPIC SURGERY - Tran, Nhat Phi; Nguyen, Le Gia Kiet; Nguyen, Van Tuan; Dang, Hong Quan; Pham, Van Nang (Cantho Journal of Medicine and Pharmacy, 2023)
Background: Rectal cancer is a common malignant disease of the digestive tract with an increasing trend in incidence, shows subtle symptoms, and is often detected at a late stage, leading to a poor prognosis due to the risk of local recurrence and distant metastasis. Objective: (1) To determine the value of magnetic resonance imaging in assessing the invasion level of rectal cancer; (2) Short-term outcomes of laparoscopic surgery for rectal cancer. Materials and method: A crosssectional, prospective study was conducted on 45 patients with rectal cancer who underwent magnetic resonance imaging and evaluation of circumferential resection margin from June 2021 to April 2023. Results: The male-to-female ratio was 1.6:1, with a mean age of 61.76 ± 11.15 (range, 37-85) years. The accuracy of determining invasion level was 60%, and that of determining CRM involvement was 62.22%. The value of MRI in diagnosing stage ≥ T3 was 58.5 times higher than that in diagnosing stage < T3. The mean operative time was 281 minutes. Postoperative anastomotic leakage was recorded in two cases and wound infection in five cases. No mortality was recorded. Conclusion: Pelvic MRI is a highly accurate imaging diagnostic tool for assessing the invasion level of rectal cancer. Laparoscopic surgery for rectal cancer is feasible and safe.